Behavioral Finance Perspective on Investment Interest of Indonesian Migrant Workers - Imas Maesaroh; Andriyansah Andriyansah (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Indonesia’s population reached 284.43 million in 2025, with 69.25% in the productive age. However, relatively low domestic income levels have encouraged labor mobility among Indonesian migrant workers. Despite higher earnings abroad, improved welfare remains limited, largely due to inadequate financial literacy and suboptimal financial behavior. This study examines the effect of financial literacy and financial inclusion on investment interest, with financial behavior acting as a mediating variable. A quantitative survey approach was employed, targeting adult respondents with investment potential. Data were analyzed using Structural Equation Modeling to assess direct and indirect relationships among variables. This research contributes to the literature by integrating a behavioral finance perspective to explain investment interest formation among Indonesian migrant workers, particularly through testing the mediating role of financial behavior. The findings reveal that financial literacy and financial inclusion significantly influence investment interest both directly and indirectly through financial behavior. The results indicate that knowledge and access to financial services do not automatically translate into investment interest, rather, behavioral mechanisms serve as a crucial linkage. These findings support behavioral finance theory, emphasizing that investment decisions are shaped by behavioral characteristics beyond purely rational considerations.